Human cathelicidin, LL-37, inhibits respiratory syncytial virus infection in polarized airway epithelial cells. (December 2016) - Harcourt, Jennifer; McDonald, Melissa; Svoboda, Pavel; Pohl, Jan; Tatti, Kathleen; Haynes, Lia
Abstract Background Respiratory syncytial virus (RSV) is a major cause of severe lower respiratory tract illness in young children worldwide. Treatment options for severe RSV disease remain limited and the development of therapeutic treatment strategies remains a priority. LL-37, a small cationic host defense peptide involved in anti-inflammatory and anti-bacterial responses, reduces replication of or infection by multiple viruses, including influenza virus, in vitro, and protects against lethal challenge with influenza virus in vivo. LL-37 also protects against RSV infection of HEp-2 cells in vitro; however, HEp-2 are not reflective of polarized airway epithelial cells and respond differently to RSV infection. An air–liquid interface (ALI) Calu-3 model that more closely mimics the human airway epithelium was established. Using this in vitro model, the effectiveness of LL-37 in preventing RSV infection and replication was examined. Results LL-37, when pre-incubated with virus prior to RSV infection (prophylactic), significantly reduced the level of viral genome detected in infected Calu-3 cells, and decreased chemokine expression associated with RSV infection in vitro. In contrast, therapeutic treatment of RSV-infected ALI Calu-3 at 24 h and 3 days post-infection had minimal impact on RSV infection. Conclusions Differences in the efficacy of LL-37 at reducing RSV infection under prophylactic and therapeutic conditions may in part be ascribed to differences in the method of peptide exposure. However, the efficacy of LL-37 at reducing RSV infection under prophylactic conditions indicates that further studies examining the efficacy of LL-37 as a small peptide inhibitor of RSV are warranted.